Diagnostic Accuracy of Adenosine deaminase enzyme (ADA) in the diagnosis of tuberculous pleural effusion - Haroon ur Rasheed , Ejaz Hassan Khan , Mohsin Shafi , Ahmad Rafiq , Ambreen Ali , Syed Luqman Shuaib, Haroon ur Rasheed , Ejaz Hassan Khan , Mohsin Shafi , Ahmad Rafiq , Ambreen Ali , Syed Luqman Shuaib (Journal of Rawalpindi Medical College, 2020)
Objective: To study the diagnostic accuracy of Adenosine deaminase enzyme (ADA) in the diagnosis of tuberculous pleural effusion (TPE). Material and Methods: It was a cross-sectional descriptive study conducted in the Pulmonology departments of Lady Reading and Khyber Teaching Hospital Peshawar and department of Pathology, Khyber Medical College, Peshawar from April 2015 to Jan 2016. A total of 210 tuberculous and non-tuberculous pleural effusion patients were selected through consecutive non-probability sampling techniques. After physical and systemic examination, 3cc of pleural fluid was taken. ADA was estimated by Non-Guisti and Galanti method through the simple colorimetric method. All the data was entered in a specially designed proforma and SPSS v16 was used for statistical analysis. Results: Out of 210 tuberculous and non-tuberculous pleural effusions, the commonest cause of pleural effusion was tuberculosis followed by malignancy. In our study, Pleural fluid ADA levels have sensitivity, specificity, positive predictive value( PPV), and negative predictive value (NPV) of 95.5%, 92.3%, 92.4%, and 96% respectively in differentiating tuberculous pleural effusions from non-tuberculous lymphocytes predominant pleural effusions. Conclusion: Tuberculosis is the commonest infectious disease worldwide. A pleural fluid ADA level of ≥ 35 U/L in lymphocyte-predominant effusions makes mycobacterium tuberculosis most likely etiology. This test is not only very sensitive and specific but also it is very cheap, quick, and easy to perform by routine colorimetric method.